Unusual CLIPPERS presentation and role of MRI examination in the proper diagnostic assessment: A case report. (2019) - Vola, Elena; Russo, Camilla; Macera, Antonio; Del Vecchio, Walter; Puoti, Gianfranco; Caranci, Ferdinando; Elefante, Andrea
Highlights: CLIPPERS is a recently described, underestimated CNS inflammatory disorder involving midbrain and cerebellum. Unusual clinical presentation can make the diagnosis particularly challenging to the clinician. MRI plays a pivotal role in the correct diagnostic assessment, helping discriminate CLIPPERS from potential mimickers. Abstract: Chronic Lymphocytic Inflammation with Pontine Perivascular Enhancement Responsive to Steroids syndrome (CLIPPERS) is a newly described, underestimated CNS inflammatory disorder involving predominantly the midbrain and the cerebellum. CLIPPERS pathogenesis is largely unknown, and its clinical manifestations are polymorphic and sometimes confounding. Recently clinical, radiological and pathological diagnostic criteria have been proposed to discriminate CLIPPERS from potential mimickers, but the diagnosis still remains challenging. Here we present the case of a patient with radiological findings consistent with CLIPPERS but with atypical clinical presentation, highlighting the importance of a proper diagnostic assessment.